A review of electrospun metal oxide semiconductor-based photocatalysts - Fushui Guo; Liantao Hao; Liu Feng; Bingjie Hu; Jinye Niu; Xuliang Zhang; Shuangying Chen; Bo Liu (iScience)
Summary: In recent years, photocatalytic materials with a nanofiber-like morphology have garnered a surge of academic attention due to their distinctive properties, including an expansive specific surface area, a considerable high aspect ratio, a pronounced resistance to agglomeration, superior electron survivability, and robust surface activity. Consequently, the synthesis of photocatalytic nanofiber materials through various methodologies has drawn considerable attention. The electrospinning technique has been established as a prevalent method for fabricating nanofiber-structured materials, owing to its advantageous properties, including the ability for mass production and the assurance of high continuity. This review focuses on metal oxide semiconductor-based materials, which are crucial components of photocatalysts. We summarize several recent studies that explore morphology modulation, surface modification, element doping, and composite construction using uniaxial and coaxial electrospinning techniques. Finally, we present potential approaches for constructing high-activity photocatalytic systems through electrospinning technique.